Logic Pro professional music production - Nahmani, David (Peachpit Press, 2025)
Record, arrange, produce, mix, and master music with this bestselling, Apple-certified guide to Logic Pro. Veteran producer and composer David Nahmani uses real-world professional Logic Pro projects to guide you through step-by-step instructions and straightforward explanations, ranging from basic music creation to sophisticated production techniques. Using a project-based approach, this book shows you how to record audio and software instruments, create musical content, and build arrangements. Youll explore Session Players to create professional drum, bass, and keyboard performances, and use the Chord track to edit your songs chord progressions. Youll use Sample Alchemy, Beat Breaker, and Quick Sampler to create stutter effects and vocal chops, and learn ear-candy production techniques, such as parallel processing and turntable start and stop effects. Youll use Flex Time to stretch audio and correct the timing of recordings, and youll tune vocals with Flex Pitch. Youll add the warmth and coloration of analog audio equipment with the mix, and automate the song with ChromaGlow, mix a song using EQ, compression, delay, reverb, and other plug-ins to achieve a professional sound. Finally, youll automate the mix and prepare the song for distribution on streaming services with Mastering Assistant.
Includes index. - "For Logic Pro 11.X."
Keywords: Logic (Computer file); Digital audio editors; Éditeurs audionumériques